Clinical analysis of 163 pediatric patients with infectious mononucleosis: a single‐center retrospective analysis - Yan Li; Kun Wang (Immunity, Inflammation and Disease)
Abstract Objective This study aims to enhance the management of Epstein‐Barr Virus (EBV) infections by analyzing the correlation between laboratory indicators and clinical manifestations in children, thereby proposing more precise diagnostic and treatment strategies. Methods In this retrospective study included 163 pediatric patients with EBV infections treated at the Children's Hospital of Soochow University from December 2017 to December 2019. Data collected through retrospective analysis included gender, age, clinical symptoms, signs, liver function tests, T‐cell subset distribution, EBV‐DNA copy numbers in plasma, and treatment outcomes. Patients were grouped based on EBV‐DNA copy numbers in plasma and hospital stay duration to compare clinical indicators across different groups. Results The dichotomous results of EBV‐DNA copy numbers in plasma showed that the two groups of children were significantly different in the number of days of fever (p = .0022), platelet count (p = .0212), ALT (p = .001), immunoglobulin IgM (p = .0039), IgG (p = .0195), TBiL (p = .025), LDH (p = 0.0001), and length of hospital stay (p < .001) were significantly different, indicating that EBV‐DNA copy numbers in plasma may be correlated with these characteristic variables. The dichotomous results of the length of hospital stay showed that the two groups were significantly increased in tonsil enlargement (p = .0024), platelet count (p = .0059), LDH (p = .0394), and ferritin (p = .0106) and EBV‐DNA copy numbers in plasma (p = 0.0361) were significantly different, This suggests a potential correlation between EBV‐DNA copy numbers in plasma and these clinical indicators. Conclusion Variations in platelet counts and lactate dehydrogenase (LDH) levels in children with EBV infections may serve as indicators of clinical outcomes.